Effect of the dielectric constant of a liquid electrolyte on lithium metal anodes. (20th March 2019) - Kim, Ju Young; Shin, Dong Ok; Chang, Taeyong; Kim, Kwang Man; Jeong, Jiseon; Park, Joonam; Lee, Yong Min; Cho, Kuk Young; Phatak, Charudatta; Hong, Seungbum; Lee, Young-Gi
Abstract: Lithium metal is considered one of the most promising anode materials for realizing high volumetric and gravimetric energy density, owing to the high specific capacity (∼3860 mAh g −1 ) and the low electrochemical potential of lithium (−3.04 V vs. the standard hydrogen electrode). However, undesirable dendritic lithium growth and corresponding instability of the solid electrolyte interphase prevent safe and long-term use of lithium metal anodes. This paper presents a simple electrolyte approach to enhance the performance of lithium metal batteries by tuning the dielectric constant of the liquid electrolyte. Electrolyte formulations are designed by changing the concentration of ethylene carbonate to have various dielectric constants. This study confirms that high ethylene carbonate content in a liquid electrolyte enhances the cycling performance of lithium metal batteries because the electric field intensity applied to the electrolyte is reduced in relation to the polarization of the electrolyte and thus allows smooth lithium plating and formation of a stable solid electrolyte interphase. We believe that this approach provides an important concept for electrolyte system design suitable to lithium metal batteries. Highlights: Electric field intensity for lithium plating is derived from interface analysis. Electrolytes with different dielectric constants are designed systematically. Confirmed enhanced cycling performance of lithium occurs with high EC content.